(untitled) (Journal of Oriental Studies, 2018)
This article is devoted to this phenomenon of recent decades as the mass culture of Japan. Nowadays, the Japanese mass culture, preserving its unique national characteristics, increasingly invades the world cultural space and begins to form the style of a new generation in both the West and the East countries. The article deals with such manifestations of Japanese mass culture as anime and manga, which have become Japan’s specialty all over the world. Also shown are various subcultures: suqueban, tekhnokozoku, yankee and bosozoku, kol, ganguro, manba, kigurumi, lolita, decora. In article paid more attention to the trend of “kawaii”, the elements of which are found in Japan everywhere, in large companies and in small shops, in the government and in municipal institutions.